SAT0088 COMPARISON OF THE INITIAL DIAGNOSTIC FINDINGS AND ONSET FACTORS OF RHEUMATOID ARTHRITIS (RA) IN ELDERLY ONSET RA AND ADULT ONSET RA BY MULTICENTER COHORT – ARE THERE ANY DIFFERENCES OF ONSET FACTORS? –. (June 2019) - Funahashi, Keiko; Matsubara, Tsukasa; Shono, Esuke; Oribe, Motohiro; Hashimoto, Keisuke; Sagawa, Akira; Yoshitama, Tamami; Mitsuka, Takeshi; Yoshida, Tomohiko; Imai, Atsuko; Miyake, Nobuaki; Ushio, Kazuyasu; et al.
Abstract : Background: In recent years, it has been reported that elderly onset RA (EORA) is a pathology different from that adult RA (AORA) 1) . It has been reported that RA is due to genetic background, and many other factors. However it is not clear whether EORA and AORA share onset factors. Objectives: We compared the initial diagnostic finding of EORA and AORA patients who were diagnosed by RA specialist at their own hospital. We also compared the presence or absence of the onset factors between EORA and AORA. Methods: 1185 patients at 18 facilities who were initially diagnosed with RA were included. EORA (n=398) was defined by disease onset at over 60 years and AORA (n=732) was defined by disease onset from16 to 59 years. We compared blood examination, clinical findings, presence of bone erosion, gender, age, and background factors pre-onset (family history, history of smoking/operation, presence of periodontal disease/gynecological diseases/digestive system diseases) between EORA and AORA. Clinical findings were analyzed with Mann-Whitney U-test and frequency of pre-onset history were analyzed by 2 × 2 Chi square test. Results: The average age of EORA and AORA were 72 years and 54 years old. The ratio of female was 75% in EORA, but 84% in AORA, a significant difference (P<0.01). The average values of CRP (ug/ml) were 2.0 in EORA, but it is 1.3 in AORA, significantly lower (P<0.001). Also ESR (mm/h) and MMP-3 (ng/ml) of EORA were 46 and 83, whereas those of AORA were 36 and 29 significant as CRP. On the other hand, TJC, SJC, PaGA and PhGA were not significantly different. We also compared the prevalence of onset factors between EORA and AORA. There was no clinical significant difference in smoking history and gynecological conditions. The presence rate of stress and family history in AORA were 71% and 38%, whereas that in EORA was 54% and 26%, significantly lower (P<0.001). On the other hand, the presence rate of history of gastrointestinal disease, periodontal disease and operation history in AORA were 43%, 36% and 40%, but those in EORA were 49%, 46% and 52%, significantly higher(P<0.01). As in previous reports 2), the ratio of men and the inflammation values in EORA were significantly higher, but there was no difference in SJC, PaGA, and PhGA. This study verified in Japanese EORA as the other reports. There were differences in the presence rate of onset factors between the two groups, while EORA had many external factors such as surgical history, whereas AORA had genetic factors and stress in their backgrounds. Regarding the presence of bone erosion, it was caused by the period from the appearance of the symptoms until the diagnosis and was unrelated to age at onset. Conclusion: This study suggests that the onset of EORA is more likely to be attributed to external factors than genetic factors. References: [1] G.Bajocchi et.al, Clin Exp Rheumatol2000; 18(suppl.20), S49-50 [2] Dejaco.Cet.al., Arthitis Care & Res2013; 65, 304-308 Disclosure of Interests: Keiko Funahashi Speakers bureau: AYUMI Pharmaceutical Corporation, Eli Lilly Japan K.K., Nichi-Iko Pharmaceutical Co., Ltd, Asahi Kasei Pharma Corporation, Tsukasa Matsubara Consultant for: Nichi-Iko Pharmaceutical Co., Ltd, Pfizer Japan Inc., Speakers bureau: Astellas Pharma Inc, SEKISUI MEDICAL CO., LTD., UCB Japan Co. Ltd, DAIICHI SANKYO COMPANY Ltd, Bristol-Myers Squibb Company, ONO PHARMACEUTICAL CO., LTD., Mitsubishi Tanabe Pharma Corporation, Celltrion Healthcare Co., Ltd, AYUMI Pharmaceutical Corporation, Eisai Co., Ltd, Janssen Pharmaceutical K.K, Pfizer Japan Inc., Asahi Kasei Pharma Corporation, AbbVie GK., Chugai Pharmaceutical Co., Ltd, Eli Lilly Japan K.K., Esuke Shono: None declared, Motohiro Oribe: None declared, Keisuke Hashimoto: None declared, Akira Sagawa Paid instructor for: ONO Pharmaceutical co., ltd, Eli Lilly Japan K.K., Takeda Pharmaceutical Company Limited, AYUMI Pharmaceutical, ISSEI PHARMACEUTICAL CO., LTD., CHUGAI PHARMACEUTICAL CO., LTD., Asahi Kasei Pharma Corporation, Janssen Pharmaceutical, Tamami Yoshitama: None declared, Takeshi Mitsuka: None declared, Tomohiko Yoshida: None declared, Atsuko Imai: None declared, Nobuaki Miyake: None declared, Kazuyasu Ushio: None declared, Izumihara Tomomaro: None declared, Tsuru Tomomi: None declared, Yosuke Nishioka: None declared, Shigeto Kiyokawa: None declared, Norihiro Nishimoto: None declared